EVALUATING ERA5 WEATHER PARAMETERS DATA USING REMOTE SENSING AND IN SITU DATA OVER NORTH RED SEA - M. Ayman; Z. Salah; K. Tonbol; M. Shaltout (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
High demand is placed on atmospheric studies specially for climatic characteristics, in order to cooperate with the government vision for exploitation of marine resources and a great potential for renewable energy, including solar, wind, hydro and geothermal energy as well as the huge expansion in coastal construction projects planned in the Egyptian Red Sea coasts for establish and growth of industry, tourism and urbanization. This study analyse the recent trends of Surface Wind (W10), surface air temperature (T2m), relative humidity (RH2m) and surface pressure (MSLP) using the European Centre for Medium-Range Weather Forecasts (ECMWF) latest fifth-generation reanalysis weather elements product global Reanalysis dataset (ERA5) Compared to Satellite Earth Observation (EO) altimetry remote sensing data (MERRA-2) and local observed data from chosen WMO automatic weather stations (AWS) over North Red Sea coasts in Egypt, Hourly data records were acquired from four WMO weather stations, deployed in different locations: Suez, Sharm Elshaikh, Safaga, Marsa Alam to study regional Climatic Characteristics, test and validate ERA5 data and evaluates the ability of ERA5 reanalysis to reproduce hourly and monthly averages for weather characteristics over North Red Sea, with hourly time series for data spans approximately 11 years, period from January 2012 to December 2022. Results of the analysis expected to reveal the agreement between remote sensing data, observations and ERA5 estimates, determine correlation values and Root Mean Square Error (RMSE). Based on certain considerations outlined in this paper, it is appropriate to use MERRA-2 and ERA5 to characterize T2m, RH, W10 and MSLP over North Red Sea.